Team Situation Awareness Within the Medical Field Context: A Scoping Review - Tianjiao Shi; Huijuan Ma; Xi Yao; Suofei Zhang; Yu Luo (Nursing in Critical Care, 2026)
ABSTRACT Background In the medical field, the lack of team situation awareness is a substantial cause of communication failures, decision‐making delays and treatment errors, particularly in emergency scenarios such as resuscitation and trauma management. Although this concept has been extensively studied in aviation and military fields, its application and efficacy in complex medical environments remain in a phase of rapid development and faces challenges. Aims To conduct a scoping review of team situation awareness research in the medical field. Study Design This scoping review followed Arksey and O'Malley's methodology framework and the PRISMA‐ScR guidelines. We searched nine electronic databases (PubMed, Web of Science, Embase, CINAHL, Cochrane Library, Wanfang Data, CNKI, VIP and CBM) from the database inception to 5 February 2026. The data from the literature were extracted, summarised and analysed by two independent researchers. Results Sixteen English‐language studies were included, one randomised controlled trial, three non‐randomised intervention or quality‐improvement studies, 10 quantitative observational or instrument‐development studies and two qualitative studies. Among the 14 quantitative studies, simulation‐based acute‐care environments were most common ( n = 8), followed by real‐world clinical settings ( n = 6). Eight studies used the Situation Awareness Global Assessment Technique (SAGAT) or a team variant, six used observational rating instruments and six used study‐specific questionnaires, similarity indices or process measures; categories overlapped because several studies used more than one approach. Interventions were categorised as technology‐assisted ( n = 1), process‐management ( n = 2) and educational strategies ( n = 1). Conclusion Evidence on team situation awareness in healthcare is moving from conceptual exploration towards tool development and implementing interventions. However, standardised measurement, real‐world validation and long‐term evaluation remain insufficient. Relevance to Clinical Practice Team situation awareness should be embedded in interprofessional healthcare education and clinical practice as a core non‐technical safety competency. This requires clinicians and nurse leaders to: (1) implement structured briefings, huddles, closed‐loop communication and shared high‐risk patient labelling to create a common understanding of patient status and care priorities; (2) incorporate team situation awareness assessment into emergency resuscitation simulations and real‐world debriefings using feasible observational or simulation‐based tools; and (3) develop interprofessional training and technology‐supported workflows that enable physicians, nurses and allied health professionals anticipate deterioration, coordinate roles and respond rapidly.